The Effectiveness of Edmodo-Based E-learning Media in Islamic Education Learning - Fitri Istin Maisyaroh; Afif Kholisun Nashoih (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
For use of edmodo in learning islamic religious education aims to describe the use of edmodo in teaching and learning based on religion. The subject of this research is the seventh semester students of islamic education at wahab hasbullah universiry. This research is a research and development and the method used is quality research and the data used is inter-observation pamotan elementary school students and islamic religious education teachers. The results of this study are classroom interactions between grade 5 elementary school students and teachers in the edmodo application, teaching and learning islamic religious education becomes interesting and students are active in learning because the teacher encourages them to use the edmodo application in writing comments, massages and also when they present in front of the class. However, there are some students mistakes when they write comments, and also when they have learning done.